A note on the effect of supplementation with noug cake (Guizotia abyssinica) on the milk production of crossbred cows - Little, D.A.; Anderson, F.M.; Durkin, J.W. (International Livestock Centre for Africa, 1987)
Reports an experiment conducted by ILCA's Nutrition programme to supplement poor quality grass or crop residues that form the basis of many ruminant diets in Africa. Emphasizes the efficient utilization of readily available resources for optimal animal production, in which the influence of noug cake supplementation on the milk production of cows fed grass hay was measured.